Indonesia-China International Dispute on the Natuna Island Case: Various International Law Discourses and Practices in Regional Countries - Chasanah, Anissaa Nuril; Arifin, Ridwan; Nte, Ngboawaji Daniel (Universitas Negeri Semarang, 2023)
The Natuna Island case stands as a focal point in the complex web of international relations, particularly between Indonesia and China, in the South China Sea region. This study explores the various international law discourses and practices adopted by regional countries concerning this dispute. Indonesia's sovereign claims over the Natuna Islands clash with China's expansive territorial assertions, leading to diplomatic tensions and legal debates. In analyzing this dispute, this study delves into the multifaceted dimensions of international law invoked by both parties and observed by neighboring states. It examines the application of principles such as the United Nations Convention on the Law of the Sea (UNCLOS) and customary international law concerning territorial sovereignty and maritime rights. Moreover, the study scrutinizes the strategies employed by Indonesia and China within international forums, including arbitration and diplomatic negotiations, to resolve their differences. It highlights the significance of multilateral cooperation and adherence to established legal frameworks in mitigating conflicts and maintaining regional stability. Furthermore, the study assesses the responses of other regional countries to the Natuna Island dispute, elucidating their stances on the applicability of international law and the preservation of their own interests amidst geopolitical tensions. These responses offer valuable insights into the evolving dynamics of maritime disputes and the role of international law in shaping regional security architectures.